PENDAMPINGAN PROGRAM ANTENATAL CARE (ANC) TERPADU MELALUI MEDIA (KIE) KOMUNIKASI, INFORMASI DAN EDUKASI DI PUSKESMAS PURWOKERTO UTARA II DALAM ERA ADAPTASI KEBIASAAN BARU - Prita Suci Nurcandrani; Pundra Rengga Andhita; Yusyida Mun Saidah; Rizki Ardhi Rahman; Raden Endah Nurkhalida (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
The priority of the Integrated Antenatal Care (ANC) program is aimed at reducing maternal mortality and morbidity, preparing the role of mothers and families to accept the birth of children so that they experience normal growth and development, and enabling mothers to exclusively breastfeed their babies. The results of the Weighing Operation for the North Purwokerto 2 Health Center in February 2021 showed that out of a total of 593 toddlers aged 0-23 months, 58 or 9.78% of them were stunted, while in September 2021 it showed that of a total of 523 toddlers aged 0-23 months, 71 or 13 ,58% of them experienced stunting. Facing this reality, proper tools, media, and communication channels are needed for the Integrated ANC Program so that the North Purwokerto 2 Health Center can still provide education and information when the face-to-face interaction model is not recommended. Assistance in IEC activities (Communication, Information and Education) is seen as very urgent considering the high stunting rate so that more in-depth intervention through the program is needed. This partnership program uses a mentoring method that begins with making a tool in the form of videography as the main guide for teams and midwives in a sustainable Integrated ANC Program. This activity resulted in six IEC media used by partners and socialization of these media to midwives in the working area of ​​the North Purwokerto 2 Health Center which includes the villages of Grendeng, Sumampir, Pabuwaran, and Karang Wangkal.